Reporting of the 1920 Turkish-Armenian War in the Armenian press - Minasyan, Edik G.; Menkouski, Viachaslau I.; Gabrielyan, Mkhitar R.; Mkhoyan, Hayk Kh.; Ghanalanyan, Tigran H. (Journal of the Belarusian State University. History, 2024)
The article studies the reporting of the events of 1920 Turkish-Armenian War in Armenian press. The corresponding analysis of the «Yaraj» (Yerevan), «Mshak» (Tiflis), «Arev» (Alexandria) and «Hayrenik» (Boston) newspaper publications for August 1920 – February 1921 allows us to find out position of Armenian socio-political circles regarding possible developments of relations and ongoing military conflict between Turkey and Armenia. It shows that Armenian political elites overestimated their own capacities and underestimated the ones of the Kemalist Turkey, and it greatly influenced the former political decisions. The support of Turkey by Soviet Russia and the inactivity of Western allies of Armenia was also widely discussed in that time Armenian press. On the one hand, the opposition press blamed the government of the Republic of Armenia for that situation, on the other hand, the periodicals of the Armenian revolutionary federation «Dashnaktsutyun» tried to show that external factors had played their decisive role, and that the defeat in the war had been inevitable. The Armenian diaspora press mostly received information with a major delay: outdated and often untrue news circulated for a long time. One of the most memorable examples was the news about the recapture of the city of Kars by the Armenians. The study of the Armenian press before the war shows that both the government of the Republic of Armenia and the main opposition forces did not found their political calculations on adequate assessments of the regional and international situation and thus made their attempts to predict the events, and they accepted their desires instead of reality. It was for this reason that the disastrous consequences of the war had an effect of a cold shower for the Armenian community.